Developing guidelines for socially sustainable indirect procurement : A qualitative case study based on key sustainability theories - Metsälä, Essi (My University, 2025)
Sustainable development has been extensively studied in recent years, but its connection to procurement has only begun to be emphasized in recent years. The sustainability of direct procurement has been studied extensively, but less attention has been paid to the sustainability of indirect procurement. Of the three dimensions of sustainability, the environmental dimension has been studied extensively, including green procurement, but the social dimension has received less attention. This study examines the key factors, challenges, and practices of socially sustainable procurement, while exploring strategies for improvement. Its aim is to develop a framework for integrating social responsibility into procurement decisions and to bridge the research gap between procurement and social sustainability. While acknowledging the environmental and economic dimensions of sustainability, the focus remains primarily on the social aspect. The study is conducted as a qualitative case study. The study uses two different data collection methods. First, seven procurement professionals are interviewed, after which internal and external materials are used to support the findings from the interviews. This is referred to as data triangulation. The data collected in the study is analyzed using qualitative content analysis. The responses are divided into thematic categories that correspond to the main dimensions of the research questions, i.e., the current situation, challenges, and opportunities. The categories have been created based on the research questions, and the aim is to find answers to them. The findings section aims to present the results for each theme. Efforts have been made to verify and evaluate the reliability of the study. Based on the results, the promotion of sustainable procurement is significantly influenced by management commitment, the expertise of the procurement organization, cooperation with suppliers, and the usability of indicators and monitoring methods. The challenges highlighted include the implementation of responsibility targets at the practical level, the fragmentation of indirect procurement, and a lack of sufficient information and resources. The study offers recommendations for developing procurement in a more strategic and responsible direction. In practical terms, this means clearer guidelines, more training, better information management, and stronger cooperation with internal and external stakeholders. The results support organizations in their efforts to integrate procurement activities and sustainable development goals in a comprehensive and systematic manner.

Kestävää kehitystä on tutkittu laajasti viime vuosina, mutta sen yhteyttä hankintaan on alettu korostaa vasta viime vuosina. Suorien hankintojen kestävyyttä on tutkittu laajasti, mutta epäsuorien hankintojen kestävyyteen on kiinnitetty vähemmän huomiota. Kestävyyden kolmesta ulottuvuudesta ympäristöulottuvuutta on tutkittu laajasti, mukaan lukien vihreät hankinnat, mutta sosiaalinen ulottuvuus on saanut vähemmän huomiota. Tässä tutkimuksessa tarkastellaan sosiaalisesti kestävän hankinnan avaintekijöitä, haasteita ja käytäntöjä sekä tutkitaan parannusstrategioita. Tutkimuksen tavoitteena on kehittää kehys sosiaalisen vastuun integroimiseksi hankintapäätöksiin ja kaventaa hankintojen ja sosiaalisen kestävyyden välistä tutkimuksen aukkoa. Vaikka tutkimuksessa tunnustetaan kestävyyden ympäristö- ja talousulottuvuudet, painopiste on ensisijaisesti sosiaalisessa ulottuvuudessa. Tutkimus toteutetaan kvalitatiivisena tapaustutkimuksena. Tutkimuksessa käytettiin kahta eri tiedonkeruumenetelmää. Ensin haastateltiin seitsemää hankinta-alan ammattilaista, minkä jälkeen haastattelujen tuloksia tuettiin sisäisillä ja ulkoisilla materiaaleilla. Tätä kutsutaan datan triangulaatioksi. Tutkimuksessa kerätyt tiedot analysoidaan kvalitatiivisen sisällönanalyysin avulla. Vastaukset on jaoteltu temaattisiin luokkiin, jotka vastaavat tutkimuskysymysten pääulottuvuuksia, eli nykytilannetta, haasteita ja mahdollisuuksia. Luokat on luotu tutkimuskysymysten perusteella, ja tavoitteena on löytää niihin vastauksia. Tulokset-osiossa esitetään kunkin teeman tulokset. Tutkimuksen luotettavuuden varmistamiseksi ja arvioimiseksi on tehty työtä. Tulosten perusteella kestävän hankinnan edistämiseen vaikuttavat merkittävästi johdon sitoutuminen, hankintaorganisaation asiantuntemus, yhteistyö toimittajien kanssa sekä indikaattoreiden ja seurantamenetelmien käytettävyys. Haasteina korostuvat vastuullisuustavoitteiden toteuttaminen käytännön tasolla, epäsuoran hankinnan hajanaisuus sekä riittävien tietojen ja resurssien puute. Tutkimuksessa annetaan suosituksia hankintojen kehittämiseksi strategisempaan ja vastuullisempaan suuntaan. Käytännössä tämä tarkoittaa selkeämpiä ohjeita, enemmän koulutusta, parempaa tiedonhallintaa ja tiiviimpää yhteistyötä sisäisten ja ulkoisten sidosryhmien kanssa. Tulokset tukevat organisaatioita niiden pyrkimyksissä integroida hankintatoiminta ja kestävän kehityksen tavoitteet kattavasti ja järjestelmällisesti.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management